A new coccoid family (Hemiptera: Coccomorpha) for an unusual species of scale insect on Podocarpus macrophyllus (Podocarpaceae) from southern China - Wu, San-An; Xu, Han (Zootaxa, 2022)
A new family, Qinococcidae Wu, fam. n., is established for the species Qinococcus podocarpus gen. n. and sp. n., collected from southern China under the bark of Podocarpus macrophyllus (Podocarpaceae). The adult female and male, egg, and all immature instars including the male pupa of Q. podocarpus sp. n. are described and illustrated. The new family is diagnosed mainly on the adult male possessing an inverted “π”-like post-tergite and unusual venation of the fore wing, with a pterostigma, posterior cubital vein and bifurcate anterior flexing patch. A key to all the developmental stages is provided.